Effects of Nonionic Micelles on the rate of Alkaline Hydrolysis Of N-(2 '-Methoxyphenyl)Phthalimide (1): kinetic and Rheometric evidence for a transition from spherical to rodlike micelles under the typical reaction conditions - Ariffin, Azhar; Sim, Y.L.; Yusof, N.S.M.; Khan, M.N. (2011)
Pseudo-first-order rate constants (k(obs)) for alkaline hydrolysis of N-(2'-methoxyphenyl)phthalimide (1) decrease nonlinearly with increasing total concentration of nonionic surfactant C(m)E(n) (i.e. [C(m)E(n)](T) where m and n represent the respective number of methyl/methylene units in the tail and polyoxyethylene units in the headgroup of a surfactant molecule and m/n = 16/20, 12/23 and 18/20) at constant 2% v/v CH(3)CN and 1.0 mM NaOH. The k(obs) vs. [C(m)E(n)](T) data follow the pseudophase micellar (PM) model at <= 50 mM C(16)E(20), <= 1.4 mM C(12)E(23) and <= 2.0 mM C(18)E(20) where rate of hydrolysis of 1 in micellar pseudophase could not be detected. The values of k(obs) fail to follow the PM model at > similar to 50 mM C(16)E(20), > similar to 1.4 mM C(12)E(23) and > similar to 2.0 mM C(18)E(20) which has been attributed to a micellar structural transition from spherical to rodlike which in turn increases C(m)E(n) micellar binding constant (K(s)) of 1 with increasing values of [C(m)E(n)](T). Rheological measurements show the presence of spherical micelles at <= 50 mM C(16)E(20), <= 1.4 mM C(12)E(23) and <= 3.0 mm C(18)E(20). The presence of rodlike micelles is evident from rheological measurements at > similar to 50 mM C(16)E(20), > 1.4 mM C(12)E(23) and > similar to 3.0 mM C(18)E(20). (C) 2011 Elsevier Inc. All rights reserved.